Tantangan Keamanan dan Strategi Adaptif Filipina Dalam Rivalitas Amerika Serikat dan Cina di Kawasan Asia Pasifik - Oktavianor, Tomi; Al Syahrin, M Najeri (Intermestic: Journal of International Studies, 2024)
The constellation and rivalry resulting in the emergence of a "dual hierarchy" between the United States and China in the Asia Pacific region triggers questions about strategy and its influence on the midde-state. This study aims to explain threats and changes in Philippine security policy that are adaptive to the conditions of the United States' rivalry with China in the Asia-Pacific Region. The research method uses a qualitative method approach through desk research from various books, journals, and mass media reports.The results show that the Philippines' adaptive strategy is a policy to respond to the impact of the United States-China hegemonic competition in the Asia-Pacific region. Compared to former president Duterte's policy of drawing closer to China by "sacrificing" security ties with the United States. Marcos Jr.'s adaptive security policy prioritizes flexible relationships. Marcos did not ally with the United States by shunning China but instead recognized China as the Philippines' strongest economic partner.